Ultrashort pulse point-by-point written aperiodic fiber Bragg gratings for suppression of OH-emission lines - Goebel, Thorsten A.; Bharathan, Gayathri; Ams, Martin; Richter, Daniel; Kraemer, Ria G.; Heck, Maximilian; Siems, Malte P.; Fuerbach, Alex; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We demonstrate the direct inscription of aperiodic fiber Bragg gratings (AFBGs) for their use as in-fiber filter elements. The modifications are induced by focusing ultrashort laser pulses with an oil-immersion objective into the fiber core. We apply an advanced point-by-point inscription technique for exible period adaptation. The fabricated AFBGs are targeted on the suppression of 10 lines in a single grating and simulations based on the specific design show excellent agreement. Furthermore, we discuss the application in astronomy as filters for the suppression of OH emission lines.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber bragg gratings; Fiber optics components; Laser materials processing; Layer-peeling algorithm; Wavelength filtering devices